Querying quantitative logic models (Q2LM) to study intracellular signaling networks and cell-cytokine interactions - Morris, Melody K.; Shriver, Zachary; Sasisekharan, Ram; Lauffenburger, Douglas A. (Biotechnology journal, 2012)
Mathematical models have substantially improved our ability to predict the response of a complex biological system to perturbation, but their use is typically limited by difficulties in specifying model topology and parameter values. Additionally, incorporating entities across different biological scales ranging from molecular to organismal in the same model is not trivial. Here, we present a framework called “querying quantitative logic models” (Q2LM) for building and asking questions of constrained fuzzy logic (cFL) models. cFL is a recently developed modeling formalism that uses logic gates to describe influences among entities, with transfer functions to describe quantitative dependencies. Q2LM does not rely on dedicated data to train the parameters of the transfer functions, and it permits straight‐forward incorporation of entities at multiple biological scales. The Q2LM framework can be employed to ask questions such as: Which therapeutic perturbations accomplish a designated goal, and under what environmental conditions will these perturbations be effective? We demonstrate the utility of this framework for generating testable hypotheses in two examples: (i) a intracellular signaling network model; and (ii) a model for pharmacokinetics and pharmacodynamics of cell‐cytokine interactions; in the latter, we validate hypotheses concerning molecular design of granulocyte colony stimulating factor. Querying Quantitative Logic Models (Q2LM) to study intracellular signaling networks and cell/cytokine interactions: The authors present a framework for building and asking questions of constrained fuzzy logic (cFL) models constructed based on prior knowledge. We demonstrate the utility of this framework for generating testable hypotheses in an intracellular signaling network model and a model for pharmacokinetics and pharmacodynamics of G‐CSF.